6-Gingerol inhibits Vibriocholerae-induced proinflammatory cytokines in intestinal epithelial cells via modulation of NF-κB. (1st September 2016) - Saha, Pallashri; Katarkar, Atul; Das, Bornita; Bhattacharyya, Aritra; Chaudhuri, Keya
Abstract: Context The effect of 6-gingerol (6G), the bioactive component of Zingiber officinale Roscoe (Zingiberaceae), in the reduction of Vibrio cholerae (Vibrionaceae)-induced inflammation has not yet been reported. Materials and methods Cell viability assay was performed to determine the working concentration of 6G. Elisa and RT-PCR were performed with Int 407 cells treated with 50 μM 6G and 100 multiplicity of infection (MOI) V. cholerae for 0, 2, 3, 3.5, 6 and 8 h to determine the concentration of IL-8, IL-6, IL-1α and IL-1β in both protein and RNA levels. Furthermore, the effect of 50 μM 6G on upstream MAP-kinases and NF-κB signalling pathways was evaluated at 0, 10, 15, 30, 60 and 90 min. Results The effective dose (ED50 ) value of 6G was found to be 50 μM as determined by cell viability assay. Pre-treatment with 50 μM 6G reduced V. cholerae infection-triggered levels of IL-8, IL-6, IL-1α and IL-1β by 3.2-fold in the protein level and two-fold in the RNA level at 3.5 h. The levels of MAP-kinases signalling molecules like p38 and ERK1/2 were also reduced by two- and three-fold, respectively, after 30 min of treatment. Additionally, there was an increase in phosphorylated IκBα and down-regulation of p65 resulting in down-regulation of NF-κB pathway. Conclusion Our results showed that 6G could modulate the anti-inflammatory responses triggered by V. cholerae -induced infection in intestinal epithelial cells by modulating NF-κB pathway.